Thulium-laser retrograde intra renal ablation of upper urinary tract transitional cell carcinoma: an ESUT Study - Bozzini, Giorgio; Gastaldi, Christian; Besana, Umberto; Calori, Alberto; Casellato, Stefano; Parma, Paolo; Pastore, Antonio; Macchi, Alberto; Breda, Alberto; Gözen, Ali Serdar; Skolarikos, Andreas; Herrmann, Thomas Reinhard William; et al. (Minerva urology and nephrology, 2021)
Thulium-laser retrograde intra renal ablation of upper urinary tract transitional cell carcinoma: an ESUT Study
Gesehen am 09.12.2021